Amine‐impregnated silica zeolite from microalgae ash at different calcination temperatures for CO2 capture. (7th September 2021) - Quan, Cui; Jia, Xiangyu; Zhang, Kouer; Zhang, Yilin; Naqvi, Salman Raza; Amin, Nor Aishah Saidina; Gao, Ningbo
Summary: Microalgae is an excellent type of biomass for bio‐energy production due to its high calorific value and fast growth. However, a large amount of ash would be generated during microalgae utilization. In this work, MCM41 was prepared from microalgae ash. The materials were calcined at different temperatures (450°C, 500°C, 550°C, and 600°C), and the effect of calcination temperature was investigated. Polyethyleneimine (PEI) was loaded in MCM41 by the impregnation method at different loading amounts (30%, 40%, 50%, and 60%). The CO2 capturing capacity was measured. The results showed that the MCM41 calcined at 450°C was the optimal material, which performed the most developed pore structure. Amine loading enhanced the CO2 capturing capacity of MCM41. The CO2 capturing capacity increased as PEI loading amount increased. The highest CO2 adsorption amount was 2.275 mmol/g with 60% amine loading at 25°C and 1 bar. Adsorption temperature had a mild impact on CO2 capture, and its CO2 adsorption amount decreased slightly with an increase in the adsorption temperature. It was considered that the CO2 uptake of amine‐impregnated MCM41 kept stable at different temperatures below 100°C. Also, it showed good cyclic stability. After 10 cycles, the CO2 capturing capacity of 1.6 mmol/g was exhibited. Abstract : Microalgae ash was used to prepare MCM41 materials. Different calcination temperatures for MCM41 preparation were investigated. Anime‐impregnated MCM41 showed remarkable CO2 capturing capacity. Stable CO2 capturing capacity was exhibited at various adsorption temperatures.